Komunikasi Politik dalam Penyusunan Program Legislasi Daerah Provinsi Riau Tahun 2015 - Raja Amin; Auradian Marta (Nakhoda: Jurnal Ilmu Pemerintahan, 2015)
This study tries to explain the political communication in the preparation Prolegda Riau Province 2015 phenomenon that occurs in the community is the information regarding the preparation of Prolegda not to society, causing a lack of community involvement in the preparation of this Prolegda Riau Province. To answer the questions in this article, the study used the theory of political communication with a qualitative research approach. Sources of information in this study was obtained from the Regional Secretariat of the Legal Bureau and the Agency Formation Riau Province Regional Regulation Riau Provincial Parliament in the form of primary and secondary data. These results indicate that the political communication used in the preparation Prolegda Riau Province in 2015 was communications group. Riau Provincial Government through the relevant agencies and the DPRD Riau Province (BPPD and the Commission) to capture the aspirations of the community using the media work meetings, hearings and meetings in the field.